Disgust as embodied loss aversion. (1st January 2017) - Schnall, Simone
ABSTRACT: A quickly expanding literature has examined the link between physical disgust and morality. This article critically integrates the existing evidence and draws the following conclusions: First, there is considerable evidence that experimentally induced disgust and cleanliness influence moral judgment, but moderating variables and attributional processes need to be considered. Second, moral considerations have substantial effects on behavioural concomitants of disgust, such as facial expressions, economic games and food consumption. Third, while disgust involves a conservation concern, it can manifest itself in both liberal and conservative political attitudes. Overall, disgust can be considered to form part of a behavioural loss aversion system aimed at protecting valuable resources, including the integrity of one's body. Recommendations are offered to investigate the role of disgust more rigorously in order to fully capture its role in moral life.